ANALYSIS OF ECONOMIC LAND RENT CHANGES ON COMMUNITY FOREST CONVERSION IN UPSTREAM CILIWUNG WATERSHED - Agus Astho Pramono (Jurnal Penelitian Sosial dan Ekonomi Kehutanan, 2010)
Puncak area is the upstream of ciliwung watershed where vegetated land conversion has been occurring excessively and uncontrolled. This research is aimed to know some problems regarding to the land conversion, especially forest conversion i.e. 1) to know the rate of forest conversion at upstream Ciliwung watershed, 2) to understand the change of economic land rent of forest conversion activities. Samples were taken through purposive sampling method and the nilai ekonomi lahan measurement was conducted using net present value approach. The result revealed that on farm forests which are commonly formed as mix garden (agroforestry) in upstream Ciliwung watershed has been reduced rapidly during 1995-2003. The remained agroforesty in a small scale can be found at Gadog and Sukakarya village. Agroforestry land usage encountered high opportunity cost, whereas land conversion to others usage increased the economic land rent up to Rp 29.940.878.588 /year in Cisarua region and Rp 41.718.102.750 /year in Megamendung region.